The stable isotope composition of organic and inorganic fossils in lake sediment records: current understanding, challenges, and future directions - van Hardenbroek, M.; Chakraborty, A.; Davies, K.L.; Harding, P.; Heiri, O.; Henderson, A.C.G.; Holmes, J.A.; Lasher, G.E.; Leng, M.J.; Panizzo, V.N.; Roberts, L.; Schilder, J.; et al. (Elsevier, 2018)
This paper provides an overview of stable isotope analysis (H, C, N, O, Si) of the macro and microscopic remains from aquatic organisms found in lake sediment records and their application in (palaeo)environmental science. Aquatic organisms, including diatoms, macrophytes, invertebrates, and fish, can produce sufficiently robust remains that preserve well as fossils and can be identified in lake sediment records. Stable isotope analyses of these remains can then provide valuable insights into habitat-specific biogeochemistry, feeding ecology, but also on climatic and hydrological changes in and around lakes. Since these analyses focus on the remains of known and identified organisms, they can provide more specific and detailed information on past ecosystem, food web and environmental changes affecting different compartments of lake ecosystems than analyses on bulk sedimentary organic matter or carbonate samples. We review applications of these types of analyses in palaeoclimatology, palaeohydrology, and palaeoecology. Interpretation of the environmental ‘signal’ provided by taxon-specific stable isotope analysis requires a thorough understanding of the ecology and phenology of the organism groups involved. Growth, metabolism, diet, feeding strategy, migration, taphonomy and several other processes can lead to isotope fractionation or otherwise influence the stable isotope signatures of the remains from aquatic organisms. This paper includes a review of the (modern) calibration, culturing and modeling studies used to quantify the extent to which these factors influence stable isotope values and provides an outlook for future research and methodological developments for the different examined fossil groups.